The Relationship Between The Work Environment and Work Motivation at PT. X (An Outsourcing Company) In Bandung, Indonesia - Ajeng Irma Setiawan; Ayuningtyas Yuli Hapsari (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
The availability of human resources has an important role to manage employees owned by the company in achieving company goals. Human resources owned by the company must be managed properly by the company, namely by developing employee skills and knowledge by providing job training, providing work motivation to employees, applying good work discipline, providing compensation for the workload, and providing an environment of comfortable work for employees and so on. One of the things that influences an employee's performance is their work environment. Employees will feel comfortable when working if the company has good workplace cleanliness, safety when working, as well as the availability of adequate work facilities to enhance employee performance. Work motivation, in addition to the work environment, is thought to be another factor that influences employee performance. Employees that are highly motivated at work are more likely to deliver excellent results. The purpose of this study is to see how the work environment, employee motivation, and employee performance at PT. X. influence each other. The descriptive and verification methodologies were utilized in the research. This study's sample was comprised of all employees at PT. X. Based on the findings of the study, it can be concluded that the work environment has a significant impact on employee performance at PT. X, that work motivation has a significant impact on employee performance at PT. X, and that work environment and work motivation have a simultaneous and significant impact on employee performance at PT. X.